Poor Eyesight: Its Effect on Academic Performance of Selected ABM Grade 12 Students In Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Poor Eyesight is one of the major problems encountered by some Grade 12 Senior High School in BCP. This study aims to know how poor eyesight affects the Academic performance of those students. The study observes that several reasons affect the students in performing well during discussion/lectures inside the class, in terms of their performance tasks and their written works. The researchers seek to know if poor vision might affect the students’ performance. The researchers also want to provide good recommendations for the results of this study. The quantitative method was used in this study using a descriptive research design. It focused on how poor eyesight affects the academic performance of Accountancy, Business and Management Students. There were three variables identified to be affected by poor eyesight in academic performance such as students’ discussion, performance tasks, and written works. The data were collected by distributing survey questionnaires to the target respondents. The result of the study reveals that poor eyesight affects the academic performance of Grade 12 students in terms of the following variables: (1) Discussion-shows that the students who can't see the visual aids lead to them not understanding the flow of discussion. (2) Performance tasks-shows that they may not actively participate in some activities in school due to their poor vision. They may find it hard to get instruction while doing activities and may cause low-performance tasks in their classes. (3) Written Works-shows that some students can't read the test papers properly. They may get the wrong information and answer them incorrectly because they can't see some words due to poor vision. It affects their academic performance because having a poor vision bothers them as students. The study recommends that the teachers or the school administrations need to provide an eye examination for those students who have poor eyesight. The study recommends that the teachers should approach those students who are suffering from poor eyesight to further help them in improving their skills and performances inside the class or school.
Keywords: poor eyesight